T Cell-Mediated Chronic Inflammatory Diseases Are Candidates for Therapeutic Tolerance Induction with Heat Shock Proteins - Barbera Betancourt, Ariana; Lyu, Qingkang; Broere, Femke; Sijts, Alice; Rutten, Victor P. M. G.; van Eden, Willem (Frontiers in Immunology, 2017)
Failing immunological tolerance for critical self-antigens is the problem underlying most chronic inflammatory diseases of humans. Despite the success of novel immuno-suppressive biological drugs, the so-called biologics, in the treatment of diseases such rheumatoid arthritis (RA) and type I diabetes, none of these approaches does lead to a permanent state of medicine free disease remission. Therefore, there is a need for therapies that restore physiological mechanisms of self-tolerance. Heat shock proteins (HSP) have shown disease suppressive activities in many models of experimental autoimmune diseases through the induction of regulatory T cells (T regs). Also in first clinical trials with HSP based peptides in RA and diabetes the induction of Tregs was noted. Due to their exceptionally high degree of evolutionary conservation HSP protein sequences (peptides) are shared between the microbiota associated bacterial species and the self-HSP in the tissues. Therefore Treg mechanisms, such as those induced and maintained by gut mucosal tolerance for the microbiota, can play a role by targeting the more conserved HSP peptide sequences in the inflamed tissues. In addition, the stress up-regulated presence of HSP in these tissues may well assist the targeting of the HSP induced Treg specifically to the sites of inflammation.